Evolution of population distribution and its influencing factors in the poverty-stricken mountainous region of Southwest China from 2000 to 2020 - Yang Chen; Majid Amani-Beni; Ruizhi Zhang; Dong Wei (Humanities & Social Sciences Communications)
Abstract Understanding the characteristics and determinants of population distribution is essential for formulating effective policies and strategies, especially in the poverty-stricken mountainous regions. This study investigates the characteristics, evolution (2000–2020), and influencing factors of population distribution in the Liangshan Yi ethnic region, a representative poverty-stricken mountainous region in Southwest China. The results reveal that: (1) Over the past two decades, the spatial pattern of population distribution has remained stable. However, the balance of population distribution has improved, as indicated by the decreasing size of the standard deviation ellipse, reflecting a more even population spread. (2) The population distribution demonstrates significant clustering in town centers, with strong positive correlations, as reflected in Moran’s I index values of 0.732, 0.708, 0.620, 0.556, and 0.554 for the years 2000, 2005, 2010, 2015, and 2020, respectively. (3) The vertical zonation pattern and the differentiation characteristics in slope and aspect play a significant role in population distribution. Over time, these factors have played an increasingly significant role in shaping the evolution of population distribution. The interaction between natural factors and vegetation is pivotal in the spatiotemporal patterns of population distribution. These factors have directly and indirectly contributed to the persistence of poverty in these mountainous areas by limiting accessibility, resource availability, and economic opportunities. The study’s results provide valuable insights for enhancing population distribution strategies in impoverished mountainous regions and informing policy-making.